ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJA SEKRETARIAT DEWAN PENGURUS KORPRI ACEH - Nur Alia; Nurdasila Darsono; Sofyan Idris (FEB - Unsyiah, 2018)
The purpose of this research is to know: (1) influence of emotional intelligence to organizational citizenship behavior of employee (2) influence organizational commitment to organizational citizenship behavior of employee, (3) influence of job satisfaction to organizational citizenship behavior employee (4) influence of emotional intelligence to employee performance (5) the effect of organizational commitment on employee performance, (6) the effect of job satisfaction on employee performance, (7) influence of emotional intelligence on employee performance through organizational citizenship behavior of employees, (8) influence of organizational commitment to employee performance through organizational citizenship behavior employee, (9) the effect of job satisfaction on employee performance through employee organizational citizenship behavior. This research was conducted at the Secretariat of the Korpri Aceh Executive Board. As for the object of this research is emotional intelligence, organizational commitment, job satisfaction, organizational citizenship behavior and organizational performance. The results show that emotional intelligence, organizational commitment, job satisfaction, OCB and employee performance has been running well. The test results proved that emotional intelligence affects employees OCB, organizational commitment affect the OCB employees, job satisfaction affect OCB employees, emotional intelligence affect on employee performance, organizational commitment also give effect to employee performance, job satisfaction given also affects employee performance and OCB employees have a positive and significant impact on employee performance and there is an indirect effect of emotional intelligence, organizational commitment and job satisfaction on employee performance through OCB employees.